1997
DOI: 10.1016/s0735-1097(96)00563-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Associated With Calcific Aortic Valve Disease

Abstract: Clinical factors associated with aortic sclerosis and stenosis can be identified and are similar to risk factors for atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
413
4
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,698 publications
(437 citation statements)
references
References 27 publications
13
413
4
7
Order By: Relevance
“…Previous studies have also reported an association of elevated serum LDL‐C with development and faster progression of AS 6, 46, 47, 48. In the present study, higher apoB/apoA‐I ratio was associated with faster AS progression independently of the level of LDL‐C, which did not reach significance level.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have also reported an association of elevated serum LDL‐C with development and faster progression of AS 6, 46, 47, 48. In the present study, higher apoB/apoA‐I ratio was associated with faster AS progression independently of the level of LDL‐C, which did not reach significance level.…”
Section: Discussioncontrasting
confidence: 92%
“…However, there is now compelling evidence suggesting that AS is an active and multifactorial disease involving numerous pathophysiological processes, such as atherosclerotic‐like processes 1, 2, 3, 4, 5. In this regard, well‐known atherosclerotic risk factors, including age, male sex, smoking, hypertension, hypercholesterolemia, obesity, metabolic syndrome, diabetes mellitus, as well as elevated plasma level of lipoprotein(a) (Lp[a]) have been associated with the development and/or progression of AS 6, 7, 8, 9, 10, 11, 12, 13, 14. A recent Mendelian randomization study also suggests a causal association between elevated LDL‐C and incidence of AS 15.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, male sex is associated with a 2‐fold increase in the risk of aortic valve disease 13. Moreover, recent work has shown sex‐related differences at the cellular level between male and female VICs isolated from fresh porcine leaflets,64 wherein male VICs appeared to be predisposed to assuming a diseased phenotype when compared to female VICs.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation is not entirely unexpected, given that CAVD has been associated with hyperlipidemia,10 and stenotic valves are rich in oxidized lipids and apolipoproteins B and E 11, 12. However, in contrast to coronary artery disease (CAD), elevated LDL is considered a relatively weak risk factor for CAVD 10, 13…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, fibrotic collagen accumulation, which leads to thickened and stiffened aortic valve leaflets and subsequent degeneration of valve function, could cause aortic stenosis (Miller et al ., 2011). The epidemiological risk factors of AVD resemble those of atherosclerosis, including elevated serum cholesterol, hypertension, smoking, diabetes, and male gender (Lindroos et al ., 1994; Stewart et al ., 1997). Low‐density lipoprotein accumulation was found in stenotic aortic valves in humans, and dietary hypercholesterolemia induced aortic valve stenosis in small animal models (Weiss et al .…”
Section: Introductionmentioning
confidence: 99%